Teaching English to Older Learners: Some Reflections Based on Practice in “Aula de Mayores” Lifelong Learning Programme - Bryla, Martyna Marika (IATED, 2019)
This paper is aimed at sharing personal reflections on teaching English to older learners (aged 55 and above) within the lifelong/U3A learning programme “Aula de Mayores” at the University of Málaga in Spain. First, the concept of lifelong learning, and particularly lifelong language learning, is explained in the light of its social benefits, such as inclusion, activating learner potential, as well as personal benefits, including the increase of self-esteem and a sense of agency. Second, the University of Málaga programme, “Aula de Mayores,” is briefly presented, taking into account its duration, membership and organizational characteristics. Finally, personal reflections based on teaching English to elementary and pre-intermediate older learners are presented, with a particular emphasis on affective aspects of the teacher-student relationships. In addition to identifying specific learning difficulties and reflecting upon effective (and less so) teaching strategies to remedy them, this paper addresses such concepts as personal motivation, cultural beliefs, and self-concept as instrumental in shaping the older learner’s language learning experience and the teacher’s role in the reinforcement of those beliefs and personal narratives that may contribute to a positive learning experience. As this paper hopes to demonstrate, respect, understanding, empathy, and personalised encouragement lie at the core of a successful lifelong learning experience, increasing the chances of students’ continuing their language education and fostering a sense of satisfaction which the acquisition of linguistic and cultural knowledge, and practical language skills brings.
La editorial autoriza el depósito en abierto en RIUMA.
Keywords: Lengua inglesa - Estudio y enseñanza; Educación permanente; Older learners; Lifelong learning; U3A; English teaching; Affective teacher-student relationships